Using mobile health in primiparous women: effect on awareness, attitude and choice of delivery type, semi-experimental - Fatemeh Moghbeli; Masood Setoodefar; Mohammad Reza Mazaheri Habibi; Zohreh Abbaszadeh; Hanieh Keikhay Moghadam; Sajedeh Salari; Leila Gholamhosseini; Meysam Fallahnezhad; Seyed Ali Fatemi Aghda (BMC, 2024)
Abstract Background One of the reasons for the increase in cesarean section is the lack of knowledge of mothers in choosing the type of delivery. The present study aimed to determine the effect of education through pregnancy application during pregnancy on awareness and attitude and choice of delivery type in primiparous women at Shahid Alavi Specialized Medical Center clinic in Mashhad. Methods This study was a semi-experimental type. Seventy primiparous pregnant women who had no restrictions for birth was selected. Sampling was randomized and purpose-based. The data collection tool was a questionnaire. The starting time of the training was considered from the end of the 27th week of pregnancy and continued with regular intervals until the end of the pregnancy. The questionnaires were completed once before the training and once after the training as a pre-test and post-test by the research units. SPSS software (version 26) and MacNemar test and descriptive statistics were used for data analysis. Results According to the results of the MacNemar test, a significant statistical difference was seen between women's knowledge and attitude after the training compared to before (p-value < 0.01). Choosing the type of birth was preferred before and after the training. But following the performance of women showed that only 62.86% of them chose natural birth. In fact, before the training, 40% and after 72.86% of women had chosen birth. Conclusion Pregnancy education and application during pregnancy is effective in reducing the choice of cesarean section, so this application with the topic of birth and cesarean section has improved the level of attitude and also the positive attitude of pregnant women towards birth. Creation of facilities and promotion of different methods of painless childbirth and training of maternity staff to perform birth is expected.